High mass flux spray quenching on an inclined surface: A novel methodology for the attainment of enhanced uniform cooling with unaltered surface morphology in transition boiling regime. (March 2019) - Lily,; Pati, A.R.; Panda, A.; Munshi, B.; Mohapatra, S.S.; Behera, A.; Saha, B.
Graphical abstract: Highlights: High mass flux spray cooling on an inclined plate enhances CHF from 1.21 – 1.46 MW/m 2 . The surface and cross- sectional temperature distribution asserts uniform cooling. The SEM and EDS analysis clearly asserts unaltered surface morphology. Abstract: The main obligation in the successful implementation of ultra-fast cooling in a manufacturing process are: (1) significant minimization of film boiling effect, (2) achievement of unaltered surface morphology and (3) uniform cooling on the surface of the plate. The literature does not reveal any methodology, which depicts simultaneously enhancement, unaltered surface morphology and uniform cooling. Therefore, in the current work, an attempt has been made to develop an appropriate cooling process depicting all the aforesaid requirements. The cooling on an inclined condition of the plate mitigates the aforesaid requirements. The result reveals that the heat removal rate enhances (CHF from 1.21 MW/m 2 to 1.46 MW/m 2 ) due to augmentation of sweeping rate of vapor film from the hot surface as inclination angle increases from 0° to 30°. Further increase of the inclination from 30° to 60° decreases the cooling rate due to reduction of droplet velocity, residence time and the replacement rate of the vapor and liquid layers. The optimum inclination of the plate to achieve the maximum average surface heat flux is 30°. In addition, the temperature distribution on the surface and across the thickness of the heat treated plate confirms uniform cooling. The SEM image and the EDS of the current heat treated metal is compared with the SEM images and EDS data of the metals cooled by potential coolants such as surfactant added water, NaCl added water and MgSO4 added water and the comparison clearly asserts unaltered surface morphology for the current case. The variation of the hardness on the surface and across the thickness clearly asserts the excellent shock absorbing characteristics.